Dimensions of vulnerability salient for health: a sociological approach. Issue 1 (1st January 2019) - Scambler, Graham
ABSTRACT: In this explicitly sociological contribution I discern and explore a number of dimensions of vulnerability with potential relevance to people's health, health-related quality of life and longevity. Reference is made here to (a) anomie, (b) alienation, (c) powerlessness, (d) marginalisation, (e) exclusion, (f) stigmatisation, (g) deviance, (h) cultural imperialism, (i) loneliness, and (j) symbolic violence. These are then explored further in light of the core sociological concepts of structure, culture and agency. In the penultimate part of the paper the mechanisms – or, "media of enactment" – that convert vulnerability into sickness, impairments and premature death are listed and discussed. The concluding paragraphs are committed to a consideration of the ramifications of the analysis for the effectiveness of policy interventions designed to protect people's health.